The Coffee Trail Planning as an Effort to Develop Coffee Agrotourism in Cibeureum Village Kuningan Regency - Ety Setiawati; Annisaa Eka Warliati; Yuke Hernawati (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
The Regent of Kuningan revealed that the typical coffee of Kuningan Regency has the potential to increase economic and tourism activities. The purpose of this study are to determine the potential and uniqueness of the plantation area and coffee factory in Cibeureum Village, Kuningan Regency. Planning a coffee trail that is in accordance with the potential and uniqueness of coffee plantations and factories so that it can become a coffee agro-tourism product and promote coffee agro-tourism. The analytical method that will be used in this research is the descriptive analysis method. The data used is qualitative data obtained from the results of the researcher's in-depth observations and interviews with related parties. Planning a coffee trail is able to combine everything into a complete coffee journey, starting from the planting process, picking coffee, selecting coffee beans, drying coffee beans, roasting coffee beans, grinding the coffee beans and finally being able to enjoy the coffee. Coffee trails must be positioned as the most interesting form of coffee tourism activity and can improve the experience of tourists, especially coffee lovers, in exploring coffee agrotourism.